Vegetative Growth of Pakcoy (Brassica rapa L.) Due to Different Dose of Bokashi and NPK Fertilizer - Ahmad Raksun; Moh. Liwa Ilhamdi; I Wayan Merta; I Gde Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Pakcoy is one of popular vegetable croop in Indonesia. Effort to increase the growth of pakcoy can be done by fertilizing. Research on the vegetative growth of fakcoy due to different dosages of bokashi and NPK fertilizer has been carried out in Terong Tawah Village, Wes Lombok Regency. The objectives of this research were to determaine: (1) vegetatif growth of pakcoy due to different dose of bokashi, (2) vegetatif growth of pakcoy due to different dose of NPK fertilizer, (3) the effect of the interaction between bokashi and NPK fertilizer on pakcoy growth. In this research a two factor design was used. The first factor was the dose of bokashi and the second was the dose of NPK fertilizer. The growth parameters were plant height, number of leaves, leaf lenght and leaf width of pakcoy. The research data was analyzed using analaysis of variance. The result showed that: (1) different dose of bokashi significantly affected plant height, number of leaves, leaf lenght and leaf width of pakcoy, (2) different dose of NPK fertilizer significantly affected plant height, number of leaves, leaf lenght and leaf width of pakcoy, (3) interaction between bokashi and NPK fertilizer has no significant effect on all measured growth parameters.